Characterization of Suitability of Coronary Venous Anatomy for Targeting Left Ventricular Lead Placement in Patients Undergoing Cardiac Resynchronization Therapy - Parin Yazdanifard; Ali Vasheghani Farahani; Saeed Sadeghian; Ali Kazemisaeid; Gholamreza Davoodi; Ahmad Yaminisharif; Mehrdad Sheikhvatan; Akbar Shafiee (Journal of Tehran University Heart Center, 2012)
Background: Differences in the quantity and distribution of coronary veins between patients with ischemic and non-ischemic cardiomyopathy might affect the potential for the left ventricular (LV) lead targeting in patients undergoing cardiac resynchronization therapy (CRT). In the current study, we assessed and compared the suitability of the coronary venous system for the LV lead placement in ischemic and dilated cardiomyopathy. Methods: This single-centre study, performed at our hospital, retrospectively studied 173 patients with the New York Heart Association class III or IV who underwent CRT. The study population was comprised of 74 patients with an ischemic underlying etiology and 99 patients with a non-ischemic etiology. The distribution of the veins as well as the final lead positions was recorded. Results: There was no significant difference between the two groups in terms of the position of the available suitable vein with the exception of the posterior position, where the ischemic group had slightly more suitable veins than did the dilated group (48.4% versus 32.1%, p value = 0.049). There was also no significant difference with respect to the final vein, through which the LV lead was inserted. Comparative analysis showed that the patients with previous coronary artery bypass grafting surgery (CABG) had significantly fewer suitable veins in the posterolateral position than did the non-CABG group (16.3% versus 38.7%, p value = 0.029). There was, however, no significant difference between the two subgroups regarding the final vein position in which the leads were inserted. Conclusion: The final coronary vein position suitable and selected for the LV lead insertion was not different between the cases with cardiomyopathy with different etiologies, and nor was it different between the ischemic cases with and without a history of CABG. Patients with a history of procedures around the coronary vessel may have an intact or recovered venous system and may, therefore, benefit from transvenous LV lead placement for CRT.